2019
DOI: 10.1111/epi.14722
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and seizures in young people with 22q11.2 deletion syndrome: Prevalence and links with other neurodevelopmental disorders

Abstract: Summary Objective The true prevalence of epileptic seizures and epilepsy in 22q11.2 deletion syndrome (22q11.2DS) is unknown, because previous studies have relied on historical medical record review. Associations of epilepsy with other neurodevelopmental manifestations (eg, specific psychiatric diagnoses) remain unexplored. Methods The primary caregivers of 108 deletion carriers (mean age 13.6 years) and 60 control siblings (mean age 13.1 years) completed a validated epilepsy screening questionnaire. A subsamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 48 publications
(127 reference statements)
0
37
1
1
Order By: Relevance
“…This represents an Table 2 The prevalence of psychiatric diagnoses in adults with 1q21 deletion or duplication and for adult controls. understudied topic in CNV research: however, a recent study has indicated that the frequency of seizures in young people with 22q11.2 deletion syndrome may be higher than suspected 35 , indicating that individuals with certain CNVs may need to be closely monitored and particularly under certain circumstances (e.g., fever). The one mirror phenotype of head size associated with this locus 6 was confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This represents an Table 2 The prevalence of psychiatric diagnoses in adults with 1q21 deletion or duplication and for adult controls. understudied topic in CNV research: however, a recent study has indicated that the frequency of seizures in young people with 22q11.2 deletion syndrome may be higher than suspected 35 , indicating that individuals with certain CNVs may need to be closely monitored and particularly under certain circumstances (e.g., fever). The one mirror phenotype of head size associated with this locus 6 was confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We are very grateful for the opportunity to reply to Dr Brunklaus’ letter regarding our paper “Epilepsy and seizures in young people with 22q11.2 deletion syndrome: Prevalence and links with other neurodevelopmental disorders.” We entirely agree that epilepsy is a clinical diagnosis and one that can be challenging to make with certainty—even in the optimal diagnostic environment.…”
mentioning
confidence: 85%
“…We went to great lengths to report the limitations of the ESQ in our article and agree that the rate of misdiagnosis—particularly for symptoms such as “staring into space”— will be much higher in cases than in controls. We do not feel, however, that this can explain the novel and interesting finding of an elevated rate of febrile seizures in children and adolescents with 22q11.2 deletion syndrome (22q11.2 DS; 24% in cases, 0% in sibling controls) …”
mentioning
confidence: 89%
“…The previous studies have shown that the prevalence of epilepsy in 22q11.2 DS ranges from 4.4% to 36.8%. 6 In addition, approximately 24% are reported to have symptomatic seizures. Interestingly, epilepsy in 22q11 DS is more often associated with developmental delay and intellectual disability.…”
mentioning
confidence: 99%
“…First, mouse models of 22q11.2DS have demonstrated erratic synaptic plasticity that subsequently resulted in abnormal neuronal excitation-inhibition. 6 Second, epilepsy in some patients is due to a structural brain lesion. Third, there are data suggesting that mutations in the Rab36 gene at position 22q11.2 may prevent neurotransmitter processing or release.…”
mentioning
confidence: 99%